Refrigeration of apheresis platelets in platelet additive solution (PAS‐E) supports in vitro platelet quality to maximize the shelf‐life. Issue Volume 61:Issue S1 (2021)Supplement (16th July 2021) - Johnson, Lacey; Vekariya, Shuchna; Wood, Ben; Tan, Shereen; Roan, Christopher; Marks, Denese C.
Abstract: Background: Refrigeration, or cold‐storage, of platelets may be beneficial to extend the limited shelf‐life of conventionally stored platelets and support transfusion protocols in rural and military areas. The aim of this study was to compare the morphologic, metabolic, and functional aspects of apheresis platelets stored at room‐temperature (RT) or cold conditions, in either plasma or supplemented with platelet additive solution (PAS). Study design and methods: Double‐dose apheresis platelets were collected in either 100% plasma or 40% plasma/60% PAS‐E using the Trima apheresis platform. One component from each group was either stored at RT (20–24°C) or refrigerated (2–6°C). Platelets were tested over a 21‐day period. Results: The platelet concentration decreased by approximately 30% in all groups during 21 days of storage ( p  > .05). Cold‐storage reduced glycolytic metabolism, and the pH was maintained above the minimum specification (>6.4) for 21 days only when platelets were stored in PAS. The surface phenotype and the composition of the supernatant were differentially affected by temperature and storage solution. Functional responses (aggregation, agonist‐induced receptor activation, clotting time) were improved during cold‐storage, and the influence of residual plasma was assay dependent. Conclusion: In vitro platelet quality is differentially affected by storage time, temperature, and solution. Cold‐storage, particularly in PAS, better maintains key metabolic, phenotypic, and functional parameters during prolonged storage.